2018
DOI: 10.1186/s12917-018-1415-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel quantitative canine species-specific point-of-care assay for C-reactive protein

Abstract: BackgroundSpecies-specific point-of-care tests (POCT) permit a rapid analysis of canine C-reactive protein (CRP), enabling veterinarians to include CRP in clinical decisions. Aim of the study was to evaluate a novel POCT for canine CRP (Point Strip™ Canine CRP Assay) run on a small in-house-analyzer (Point Reader™ V) using lithium heparin plasma and to compare assay performance to an already established canine CRP assay (Gentian Canine CRP Immunoassay) run on two different bench top analyzers serving as refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 36 publications
5
27
0
Order By: Relevance
“…However, it also suggested that serum CRP levels higher than those seen in healthy control dogs obviously indicate higher levels of inflammation. While the evaluation of serum CRP levels must be considered in the context of the clinical disease condition, we suggest that CRP levels assayed by our ELISA can distinguish noninflammatory and inflammatory conditions using approximately 5 µg/mL as the cut-off value (mean + 3SD: 1.1 + 3 × 1.3 μg/mL) based on the results for the control group, and equivalent cut-off values (5.5 µg/mL) were seen with the Laser assay in this study and in previous reports [ 11 , 12 ].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…However, it also suggested that serum CRP levels higher than those seen in healthy control dogs obviously indicate higher levels of inflammation. While the evaluation of serum CRP levels must be considered in the context of the clinical disease condition, we suggest that CRP levels assayed by our ELISA can distinguish noninflammatory and inflammatory conditions using approximately 5 µg/mL as the cut-off value (mean + 3SD: 1.1 + 3 × 1.3 μg/mL) based on the results for the control group, and equivalent cut-off values (5.5 µg/mL) were seen with the Laser assay in this study and in previous reports [ 11 , 12 ].…”
Section: Resultssupporting
confidence: 80%
“…3). Because the ICA produced negative results for samples with a level lower than 11.7 µg/mL and weak positive results for samples with a level higher than 6.0 µg/mL, the cut-off value of the ICA was suggested to be approximately 5-10 µg/mL, which is comparable to the cut-off values of commercial assays [11,12]. The cut-off value of the ICA was confirmed using diluted serum samples known CRP levels as approximately 5 µg/mL agreed with the results of clinical samples, producing negative results for samples with a level lower than 4.3 µg/mL and positive results for those with a level higher than 4.4 µg/mL ( Table 1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Linearity under dilution was investigated by visual inspection of the correlation of observed SAA values plotted against a calculated (expected) SAA concentration. Percent recovery rate (RR) was calculated using the difference between actual and theoretical SAA concentration, as described for canine C-reactive protein (CRP) 14 :…”
Section: Methodsmentioning
confidence: 99%
“…The stock solutions were prepared as described previously. 19 The stock solution of the lipid emulsion was further diluted such that a final concentration of 4 g/L (dog) and 2 g/L (cat) was obtained, if necessary. Samples were analyzed in triplicate in random order.…”
Section: Methodsmentioning
confidence: 99%